Extraction and characterisation of pigment from Yanzhiguo [Prunus napaulensis (Ser.) Steud.] - Pingping Shi; Haibo Luo; Qiuqiu Huang; Changliang Xu; Xiuzi Tong; Hui Shen; Huosheng Su; Hongmei Pu; Haidan Wang; Lijuan Yu; Hong Li (PeerJ, 2023)
Yanzhiguo [Prunus napaulensis (Ser.) Steud] belongs to Rosaceae family and is consumed as wild fruit, pulp and juice. However, its potential for extracting natural pigment has not yet been explored. Herein, the components in the fresh Yanzhiguo pulp were preliminarily analyzed by liquid chromatography coupled to mass spectrometry. And, the optimal pre-treatment conditions were established for further extraction of Yanzhiguo pigment based on the a* value. Then, by combining the data from single-factor experiments and response surface methodology, the optimal extraction process was established as: 35% EtOH, a liquid-solid ratio of 200:1 mL g−1, an extraction time of 65 min, and an extraction temperature of 100 °C. Moreover, it was found that the a* value and yield had high fitness except when extracted into ethanol (EtOH) with different concentrations. Meanwhile, our result demonstrated Yanzhiguo pigment had high stability in general environments with carmine (a synthetic pigment) as control, except for extreme environments such as direct (hot) sunlight, high temperature (75 °C) and strong alkaline (pH $≥$≥ 11). Also, Yanzhiguo pigment exhibited good antioxidant activity. Our results contribute to more information on Yanzhiguo pigment and promote its application by providing efficient extraction technology.